2003
DOI: 10.1292/jvms.65.1369
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Isotonic and Hypertonic Sodium Bicarbonate Solutions on Acidemic Calves Experimentally Induced by Ammonium Chloride Administration

Abstract: ABSTRACT. The objectives of this study were to evaluate and compare the effects of intravenously (IV) administered infusion of isotonic solution (ISB) or hypertonic sodium bicarbonate solution (HSB) on acid-base equilibrium and the plasma osmolarity in acidemic calves experimentally induced by 5 M-NH 4 Cl, IV infusion (1.0 ml/kg, over 1 hr). The ISB and HSB infusion induced progressive and significant increases in their HCO 3 -and BE levels that persisted throughout the period of fluid administration. The plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…NaHCO 3 contained in BRS is the most biologically suitable alkalinizing reagent for its prompt alkalization effect [14], because HCO 3 Ϫ can be directly produced from NaHCO 3 without a metabolic process. Several investigators reported concerning the efficacy of NaHCO 3 on acidosis [15][16][17][18]. In the present study, we evaluated the effects of several RS, BRS, ARS, LRS, and RS, on metabolic acidosis, serum electrolyte abnormality and circulatory failure in haemorrhagic shock model with dogs, an experimental animal model mimicking massive bleeding.…”
Section: Discussionmentioning
confidence: 96%
“…NaHCO 3 contained in BRS is the most biologically suitable alkalinizing reagent for its prompt alkalization effect [14], because HCO 3 Ϫ can be directly produced from NaHCO 3 without a metabolic process. Several investigators reported concerning the efficacy of NaHCO 3 on acidosis [15][16][17][18]. In the present study, we evaluated the effects of several RS, BRS, ARS, LRS, and RS, on metabolic acidosis, serum electrolyte abnormality and circulatory failure in haemorrhagic shock model with dogs, an experimental animal model mimicking massive bleeding.…”
Section: Discussionmentioning
confidence: 96%
“…1.3% isotonic sodium bicarbonate solution is used to treat metabolic acidosis and prevent contrast-induced nephropathy. [151617] The solution is suitable for tackling the metabolic acidosis due to lack of chloride ion. The existence of chloride ion in crystalloid solutions leads to worsening acidosis caused by hemorrhages.…”
Section: Introductionmentioning
confidence: 99%
“…Oral rehydration fluids are administered on a daily basis to dehydrated calves in veterinary practice. If treatment with oral fluids is unsuccessful, intravenous restoration for the acid-base disorder is performed [6][7][8]. Although lactated Ringer's solution is used to replace the volume of total body water and to correct to electrolyte status in small animals and horses, it dose not usually correct the metabolic acidosis in calves with severe diarrhea [6,11,12,15,16].…”
mentioning
confidence: 99%
“…Although lactated Ringer's solution is used to replace the volume of total body water and to correct to electrolyte status in small animals and horses, it dose not usually correct the metabolic acidosis in calves with severe diarrhea [6,11,12,15,16]. Sodium bicarbonate is specifically effective for acute and severe metabolic acidosis because it has rapid effect when given intravenously [7,9,15,16]. Nevertheless, rapid administration or an overdose of sodium bicarbonate solution has been associated with paradoxical cerebrospinal fulid acidosis, leftward shift of the oxyhemoglobin dissociation curve leading to decreased downloading of oxygen, intracellular shift of potassium in exchange for hydrogen ions causing hypokalemia, tetany due to decreased ionized calcium, and overshot alkalosis [2,5].…”
mentioning
confidence: 99%